1981
DOI: 10.1192/bjp.139.4.284
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Continuation Therapy Following Electroconvulsive Therapy

Abstract: Thirty-eight depressed patients who were treated with ECT were randomly assigned to receive lithium therapy or identical-looking placebo tablets for one year after clinical recovery in a double-blind trial. The patients who received placebo tablets spent an average of 7.8 weeks with an episode of depression (either as in-patients or day-patients) during the year. In comparison, patients who received lithium spent on average 1.7 weeks with an episode (P less than 0.02). The trial confirms the high rate of relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…In the first prospective study of lithium continuation therapy following ECT, a group of 38 patients who had responded to ECT were studied (Coppen et al 1981; Abou-Saleh and Coppen 1988). The patients were randomly allocated to receive either placebo or lithium therapy for 1 year.…”
Section: Lithium As a Continuation Treatment Following Ectmentioning
confidence: 99%
“…In the first prospective study of lithium continuation therapy following ECT, a group of 38 patients who had responded to ECT were studied (Coppen et al 1981; Abou-Saleh and Coppen 1988). The patients were randomly allocated to receive either placebo or lithium therapy for 1 year.…”
Section: Lithium As a Continuation Treatment Following Ectmentioning
confidence: 99%
“…Some studies have shown a neurotoxic interaction between lithium and ECT, and others have shown no significant increase in the incidence of complications [25–27]. Although both lithium and ECT can independently produce a delirium, Penney et al found that concurrent lithium and ECT is associated with an increased incidence of severe or prolonged confusion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lethargy, prolonged confusion and prolonged or recurrent seizures have been reported [101]. Although several case series have not supported an increased risk of these complications with the combined use of lithium and ECT [102][103][104], some authors do not recommend their concurrent use [101]. The American Psychiatric Association recommends either discontinuation of lithium or a reduction in dosage when ECT is initiated [105,106].…”
Section: Lithiummentioning
confidence: 99%